Automotive Chassis Engineering - Barton, David C.; Fieldhouse, John D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Written for students and practicing engineers working in automotive engineering, this book provides a fundamental yet comprehensive understanding of chassis systems and requires little prior knowledge on the part of the reader. It presents the material in a practical and realistic manner, using reverse engineering as a basis for examples to reinforce understanding of the topics. The specifications and characteristics of vehicles currently on the market are used to exemplify the theory's application, and care is taken to connect the various topics covered, so as to clearly demonstrate their interrelationships. The book opens with a chapter on basic vehicle mechanics, which include the forces acting on a vehicle in motion, assuming a rigid body. It then proceeds to a chapter on steering systems, which provides readers with a firm understanding of the principles and forces involved under static and dynamic loading. The next chapter focuses on vehicle dynamicsby considering suspension systems-tyres, linkages, springs, dampers etc. The chapter on chassis structures and materials includes analysis tools (typically, finite element analysis) and design features that are used to reduce mass and increase occupant safety in modern vehicles. The final chapter on Noise, Vibration and Harshness (NVH) includes a basic overview of acoustic and vibration theory and makes use of extensive research investigations and practical experience as a means of addressing NVH issues. In all subject areas the authors take into account the latest trends, anticipating the move towards electric vehicles, on-board diagnostic monitoring, active systems and performance optimisation. The book features a number of worked examples and case studies based on recent research projects. All students, including those on Master's level degree courses in Automotive Engineering, and professionals in industry who want to gain a better understanding of vehicle chassis engineering, will benefit from this book.
Vehicle Mechanics -- Steering Systems -- Suspension Systems & Components -- Noise, Vibration & Harshness (Nvh) -- Chassis Structures.
Keywords: Automotive engineering; Multibody systems; Vibration; Mechanics, Applied; Engineering design; Manufactures; Automotive Engineering; Multibody Systems and Mechanical Vibrations; Engineering Design; Machines, Tools, Processes